ANALISIS DETERMINAN PENERIMAAN OPINI GOING CONCERN AUDITOR - Ibnu Nugroho (Parsimonia - Jurnal Ekonomi dan Bisnis, 2015)
This study aims to prove determinant of auditor's going concern opinion. Determinants of auditor's going concern opinion in this study consists of two factors, financial and non-financial factors. The sample used in this study is the manufacturing sector companies listed on the IDX from 2011 to 2015. This study uses the method of logistic regression analysis to examine the research hypothesis. The results of this study prove that three financial factors tested, liquidity and leverage does not affect to auditor's going concern opinion. While profitability negatively affect to auditor's going concern opinion. The results of the testing of four non- financial factors, proved that the reputation of public accounting firm, audit tenure, and disclosure does not affect to auditor's going concern opinion. While the going concern opinion in the previous year has positive effect to auditor's going concern opinion.